Perancangan Sistem Informasi Presensi Pegawai Puskesmas Menggunakan Metode User Centered Design - Ririn Mulyani; Agun Guntara (Universitas Methodist Indonesia, 2026)
The development of technology has encouraged various institutions to implement innovations in attendance management systems to improve the efficiency and accuracy of attendance recording. This study aims to design a prototype of a web-based attendance system for non-civil servant (Non-ASN) employees at Puskesmas Cimalaka as a solution to the need for a more effective, accurate, and structured attendance recording process. The method used in this study is User Centered Design (UCD), with Non-ASN employees serving as the primary users of the system. Data were collected through interviews and observations to identify the context of use, existing problems, and user requirements, which were then formulated into functional requirements as the basis for system design development. The resulting prototype includes features such as login, dashboard, shift selection, attendance based on facial recognition and location, attendance history, leave requests, and activity reports. The designed user interface successfully represents users workflows and supports personnel administration processes more efficiently. Prototype evaluation was conducted using the System Usability Scale (SUS), which indicated that the proposed user interface has a good level of usability and falls within the Excellent and Acceptable categories. Therefore, the UCD approach proved effective in producing a system design that aligns with user needs and operational conditions at Puskesmas Cimalaka.